The Value of Black Monukka, Perlette, Ruby Seedless and Sultanina as parents for breeding Raisin Grapes - Evans, E. P.; Smit, C. J. (South African Journal of Enology and Viticulture, 2017)
The seedless grape cultivars Black Monukka, Perlette, Ruby Seedless and Sultanina were used as pollen parents and hybridized with two muscat flavoured and four neutral flavoured cultivars and selections in an effort to breed seedless table grapes. The progeny of some of these crosses were also evaluated for raisin quality during the 1983/84 season. Ten seedless selections and 21 selections possessing trace seeds (1-2 mm) obtained a quality rating comparable to that of Merbein Seedless, Fiesta, Perlette and Sultanina raisins. Perlette produced four times as many seedlings with satisfactory raisin quality as all the other crosses combined. The cross CG 1272 X Sultanina produced five promising white currant types. Selection CG 1272 appears to be a valuable parent for breeding improved currant types.